Nusselt number and friction factor correlations for laminar flow in parallelogram serpentine micro heat exchangers. (October 2018) - Liou, Tong-Miin; Wang, Chun-Sheng; Wang, Hsun
Highlights: Heat transfer in parallelogram serpentine micro heat exchangers is firstly explored. Effects of aspect ratio ( α ), included angle ( θ ), and Reynolds number ( Re ) are studied. A new finding is that there exists a critical value of α for Nusselt number ( Nu ). A critical Re is found for Fanning friction factor ( f ) as well. Nu and f correlations are newly proposed as composite functions of α, θ, and Re . Abstract: The topic of compact micro heat exchanger is one of the most active areas in heat and mass transfer research today. However, there is a lack of literatures on serpentine channels with parallelogram cross-section. This article provides numerical study of the hydraulic and thermal performance in parallelogram serpentine channels with aspect ratios ( α ) ranging from 0.25 to 4 and wall included angles ( θ ) ranging from 45° to 90°. The Reynolds number ( Re ), characterized by channel hydraulic diameter and mean bulk velocity, is varied from 100 to 300. Their influences on the fluid flow and heat transfer characteristics are investigated under constant wall temperature condition. It is newly found that Nusselt number ( Nu ) distributions on bottom and top walls in slant wall channels ( θ  ≠ 90°) are asymmetric and there exists a critical value of α and Re for Nu and Fanning friction factor ( f ), respectively. Furthermore, two new correlations for overall Nu and f with respect to α, θ, and Re are proposed for laminar flow in parallelogram channels, with maximum errors less than 10% and 20%, respectively, compared with numerical results.